Coup d’œil sur la recherche : Implantation d’un programme de formation à l’offre active de services en français auprès des futurs professionnels de la santé et des services sociaux dans une université canadienne. - Consortium national de formation en santé; van Kemenade, Solange (2022)

Nursing students’ well-being: A comparison of two canadian nursing programs in different linguistic contexts - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Vigier, Darcelle; Waddell, Candice; Graham, Jan Marie (Linguistic Minorities and Society, 2022)
Nursing programs are highly competitive and stressful environments; nursing educators are looking for ways to mitigate the negative consequences of demanding training programs. This article explores and compares the mental health status and sociodemographic and personal characteristics that influence the psychological distress of nursing and non-nursing students learning in either official language of Canada. An online and paper survey was administered during class time to 990 students, 186 of whom were in an undergraduate nursing program in one of two postsecondary institutions in Manitoba, Canada. Findings demonstrate that students in nursing programs are more likely to report poor mental health than students in other undergraduate programs and that nursing students in the French-language institution report poorer mental health outcomes as compared to nursing students in the English-language institution. Life satisfaction and high self-esteem are positively associated with well-being, whereas age, gender, and learning in a second language are risk factors contributing to anxiety. Keywords: mental health, risk behaviour, nursing students, linguistic minority, risk factors

Identité ethnolinguistique et bien-être mental : le cas des jeunes francophones du Manitoba - Levesque, Annabel; Gueye, Ndeye Rokhaya; de Moissac, Danielle; Archambault, Hélène; Rivard, Étienne (Alterstice, 2022)
L’identité collective est reconnue comme un facteur important pouvant contribuer au bien-être mental des individus appartenant à des minorités ethnolinguistiques. Or peu de recherches ont porté sur le cas des jeunes francophones en contexte minoritaire canadien, notamment les francophones du Manitoba. Cette recherche visait donc à analyser la relation entre le bien-être mental des jeunes francophones du Manitoba et trois dimensions de l’identité ethnolinguistique, soit l’attachement à l’identité francophone, l’attachement à l’identité anglophone et la perception de continuité ethnolinguistique. Un total de 545 francophones du Manitoba, âgés de 14 à 25 ans, ont répondu à un questionnaire. Les résultats révèlent que, bien qu’elles soient liées, les trois dimensions de l’identité ethnolinguistique en contexte francophone minoritaire représentent bel et bien des construits distincts. Par ailleurs, chacune de ces dimensions est liée de façon positive au bien-être mental des répondants. En somme, ces résultats illustrent l’importance de maintenir les efforts visant à promouvoir la vitalité ethnolinguistique des communautés francophones minoritaires et à soutenir les jeunes dans leur quête visant à intégrer leurs identités multiples. Mots-clés : identité ethnolinguistique, attachement identitaire, continuité ethnolinguistique, bien-être mental, francophones minoritaires

Official Language Minority Communities in Ontario: Understanding the Lived Experiences of Francophone Patients and their Nursing Care Providers - Muray, Mwali (2022)
Although Canada is a bilingual country, official language minority community patients struggle to access quality care in their language. This reality has been of concern for Francophone minority communities in Ontario, but has seldom been examined in a nursing context. This research sought to examine the lived experiences of registered nurses and nursing students providing care to French-speaking patients in Ontario, as well as the realities of Francophone patients seeking French language health care services in Ontario. The conceptual frameworks guiding the study were the “Four Levels of Change for Improving Quality” model and the “Four-Level Model of the Health Care System.” Using qualitative phenomenological inquiry, as influenced by Martin Heidegger and Max van Manen, 31 semi-structured interviews were conducted with three subsets (n=10 Francophone patients; n=10 nursing students; n=11 registered nurses) throughout Ontario who had experience with the phenomenon being investigated. Data collection took place over a year (2018-2019) and was analysed thematically. Significant findings were identified across the three groups. Participants revealed the patchwork of individual actions taking place to remedy the existing gaps regarding care for Francophone minority populations. This included navigating a health care system where good enough care was the unfortunate standard for Francophone patients, and discussing how Francophone patients and nursing care providers implement strategies individually to manage the lack of resources for Francophone patient populations in Ontario. This thesis asserts that official language minority communities and their nursing care providers remain faced with difficulties providing and receiving care in Ontario. While numerous structures and resources exist to remediate the problems, these interventions and resources are not always implemented systemically, leading to a disproportionate burden on individuals, significant risks for safety for patient populations, and ethical dilemmas for nursing care providers. Recommendations are provided to bridge the gaps and ensure considerations of the needs of linguistic minorities throughout the health care system. Keywords: Francophonie, Linguistic Minorities, Nursing, Phenomenology, Qualitative Research